2011
DOI: 10.1177/0265532211398110
|View full text |Cite
|
Sign up to set email alerts
|

Effects of test-taker characteristics and the number of participants in group oral tests

Abstract: This study explores the nature of co-constructed interaction in group oral tests by examining whether a test-taker's own and his or her group members' extraversion levels and oral proficiency levels have different influences on conversational styles between two group sizes: groups of three and groups of four. Data were collected from 269 Japanese upper-secondary school students, who took group oral tests either in groups of three or four. All sessions were video-taped and transcribed following Conversation Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 48 publications
1
51
2
Order By: Relevance
“…A possible reason for contradictory findings between this study and the previous studies (e.g., KondoBrown, 2002;Nakatsuhara, 2011;Winke & Gass, 2013) could be the use of different raters in different assessment settings and different test items and tasks. For example, Kondo-Brown (2002) used only trained raters in assessing test takers' writing ability, and Winke and Gass (2013) used raters from Spanish, Chinese and Korean backgrounds.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…A possible reason for contradictory findings between this study and the previous studies (e.g., KondoBrown, 2002;Nakatsuhara, 2011;Winke & Gass, 2013) could be the use of different raters in different assessment settings and different test items and tasks. For example, Kondo-Brown (2002) used only trained raters in assessing test takers' writing ability, and Winke and Gass (2013) used raters from Spanish, Chinese and Korean backgrounds.…”
Section: Discussioncontrasting
confidence: 95%
“…Various groups of raters may differ in the judgment of learners' second language ability depending on their backgrounds and the criteria they apply (Barrett, 2001). Several studies have found differences between inexperienced and experienced raters in their scorings and their use of rating strategies (Khabbazbashi, 2017;Nakatsuhara, 2011;Winke & Gass, 2013). Khabbazbashi (2017) compared the ratings of trained and untrained raters from two various backgrounds: experienced English teachers and non-teachers.…”
Section: Raters' Background In Oral Performance Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to the effects of interlocutor traits, research suggests that the test takers' familiarity with other test takers (O'Sullivan, 2002), as well as personality (level of extraversion), English proficiency level, and the number of participants, may influence test takers' performance in group discussion 11 tasks, as shown in a study on Japanese secondary school students conducted by Nakatsuhara (2011). On the other hand, Ockey, Koyama, and Setoguchi (2013) investigated the effect of interlocutor familiarity on test takers' performance in a Japanese university.…”
Section: Iii2 Paired and Group Oral Discussionmentioning
confidence: 99%